Research for Willingness to Pay for One QALY Gain - Ohkusa, Yasushi; Sugawara, Tamie (Iryo To Shakai, 2006)
Objective: The monetary evaluation of QALY gain is necessary and important for medical and public health policy decision-making. Even though one piece of empirical research has been conducted about this, the research used direct methods to estimate WTP and thus encountered a great deal of problems. This paper aims to study the same topic using conjoint analysis. Material and Method: A survey was conducted in 2005 and questionnaires were distributed to and collected from 773 households. The response rate was 88%. The subjects were 1,297 adults over age 20. In addition to socio-economic characteristics, in this survey respondents were asked a hypothetical question for conjoint analysis purposes: whether they would agree to medical care under a hypothetical situation in regards to cost, duration, number of patients, and health status. We also performed a sensitivity analysis in regards to explanatory variables in the estimation equation, discount factors, and QOL evaluation for health status. Results: In all the estimations, the estimated coefficients of total cost are significantly negative and those of QALY gain are significantly positive. The WTP per QALY gain is estimated to be 6.35 to 6.75 million yen. Income does not affect WTP per QALY significantly. Discussion: The WTP per QALY obtained in this paper is slightly higher than in the previous one, but it is worth noting that the difference between them is minor. This finding suggests that there is strong evidence for WTP per QALY being around 6 to 7 million yen.